Analysis of Functionally Graded Piezoelectric Cylinders in a Hygrothermal Environment (Advances in Applied Mathematics and Mechanics, 2014)
This paper presents an analytical solution for the interaction of electric potentials,electric displacement, elastic deformations, and describes hygrothermal effect responsesin hollow and solid cylinders, subjected to mechanical load and electric potential. Exactsolutions for displacement, stresses and electric potentials in functionally gradedpiezoelectric material are determined using the infinitesimal theory. The material propertiescoefficients of the present cylinder are assumed to be graded in the radial direction by apower law distribution. Numerical examples display the significant of influence of materialinhomogeneity. It is interesting to note that selecting a specific value of inhomogeneityparameter can optimize the piezoelectric hollow and solid cylinders responses, which willbe of particular importance in modern engineering designs.